Human Capital Strategy Implementation on Duck Nugget Frozen Food Business Over Start-Up Business Plan - Rizaldy Baskara; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2019)
Food industry it’s one of the centerpiece industry sectors as a private sector to increase national economic growth rate. Accordingly, PT. BEFINDO FOOD prefers to focus on food industry, specifically frozen food. The variants of processed food are potatoes, sausages, and nuggets also favored food by most Indonesians. However, duck meat as an one of protein source and familiar in Indonesian market due to contains high fat amount and cholesterol. In the fact, when the cholesterol of skin-off duck is compared to the chicken cholesterol it is proved that the amount of cholesterol from both ingredients are nearly similar and it is still considered healthy. Therefore, to encourage consumers to choose duck meat, the company need to reduce fat amount with smell in the production process. In addition, PT. BEFINDO FOOD needs to develop an innovation in the processing phase. In this study, PT. BEFINDO FOOD will develop the human capital in order to create qualified men who will involve in the duck nugget production.